On the wonders of replication: A student perspective - Klevjer, Kristoffer (Septentrio Conference Series, 2019)
Watch the VIDEO. The lack of replicating research is not new, still the recent "replication crisis" has made a large impact in the social and life sciences which subsequently increased their replication efforts. Most scholars do agree on the need for solid, preregistered, direct replications. However, performing them is less common, after all, researchers have their own ideas! Underestimated is though, that replications are beneficial for science, the students and supervisors! As a part of my master's thesis I performed a direct replication – and this turned into one of the most educational parts of my whole psychology degree. It was an excellent introduction to the importance of a solid method section, to Open Science and preregistration. It changed the way I read and evaluate articles. I learned the distinction between confirmatory and exploratory hypotheses. It highlighted the need for strict adherence to data collection protocols. It taught me the publishing process in a nutshell by starting data collection only after my protocol and procedures was approved by external researchers. I argue that replication are beneficial for supervisors too. Students get a thorough introduction to said concepts, which increases confidence in their work (ethics) and trust in science. Replications are time-effective alternatives for bachelors students. Supervisors can exchange ideas with other supervisors as well as use this for networking In sum, science needs it, students like and learn from it, and it is convenient and helpful for supervisors. Next time: please pitch a replication project to your student!